Eating disorders and dysfunctional attitudes in women working for public vs. private organizations - Rus, Mihaela; Sandu, Mihaela Luminita; Calin, Mariana Floricica; Dulgheru, Ioana Alexandra; Folipescu, Alexandra; Purice, Diana (Technium Social Sciences Journal, 2022)
There is a common view that eating disorders are a lifestyle choice. Eating disorders are a serious and often fatal disease. Food obsessions, body weight and fitness can also signal an eating disorder. Common eating disorders include anorexia nervosa, bulimia nervosa, nocturnal eating syndrome, otherwise unspecified eating disorders, and overeating disorders. Eating disorders occur in men and women, young and old, rich and poor, and from all cultural backgrounds; they have resulted in about 7,000 deaths a year since 2010, making them the mental illness with the highest mortality rate. The chances of recovery increase as they are detected earlier, so it is important to be aware of some of the warning signs of an eating disorder. More than seven million girls and women and one million boys and men will suffer from an eating disorder during their lifetime. Up to 3.7% of women will be diagnosed with anorexia nervosa and it is estimated that 4.2% will have bulimia nervosa. Anorexia is often associated with denial of disease and resistance to treatment.